Ancestor worship - is it Biblical? - Bae, Choon Sup (HTS teologiese studies, 2008)
Ancestor worship is practiced in different forms around the world today, even in societies participating in the modern global economy. Ancestral beliefs are deeply dependent on the premise that the souls of the dead may return to the living and influence their lives; that it is possible and acceptable for the living to communicate with the dead and lastly that the living are able to exert an effect on the destiny of deceased ancestors. The following issues are most relevant to ancestor worship: 1) death and the afterlife, 2) possibility of communication between the living and the dead, and 3) the destiny of believers who die. The article looks at these issues from a Biblical perspective, offers Biblical guidelines in assessing ancestor worship and its cosmology and interprets ancestor worship theologically. The conclusion is that ancestor worship is incompatible with Christian faith.